Drying of Rosella (Hibiscus sabdariffa) Flower Petals using Solar Dryer with Double Glass Cover Collector - Tjukup Marnoto (Chemical Engineering Diponegoro University, 2014)
Chemical ingredients in rosella petals are very beneficial for health. Rosella petals needed to be drained for storage and packing purpose. The traditional drying takes 5 days and less healthy. Solar dryer technology can speed up the drying process and protect materials from dust contamination. Solar dryer with double glass covered collector has been designed and made for drying of agricultural products such as rosella flowers. Rosella petals as much as 2300 grams with initial moisture content of 90.84 % be dried with this dryer until the moisture content of 7.67 % takes only 2 days, although the weather was less sunny . The temperature in the drying chamber was not more than 50° C, so it was good for drying groceries, not damaging chemical ingredients. The relative humidity in the space dryeris was about 40 % and it was still relative low. Drying rate and drying performance was expressed by the efficiency and Specific Moisture Evaporation Rate ( SMER ) were influenced by water content of the dried material and weather. Daily efficiency at the first and the second day: 14.931 % and 5.78%, while the daily SMER on the first and the second day: 0.222 and 0.0256 ( kg / kWh ).